The Role of Self-control and Grit in Domains of School Success in Students of Primary and Secondary School - Oriol, Xavier; Miranda, Rafael; Oyanedel, Juan C.; Torres, Javier (Frontiers in Psychology, 2017)
Objective: Self-control and grit have become two of the most important variables that explain success in different aspects of people’s daily life (Duckworth & Gross, 2014). Self-control promotes delayed gratification and directly influences thoughts, emotions and impulses. On the other hand, grit enhances the achievement of goals through perseverance even before extreme external circumstances. Since both constructs are related, examining them together is compelling, as long as the different nuances that characterize each are taken into account. Two structural equation models (SEM) were conducted to observe the effect of self-control and grit on a more specific indicator of academic success (academic self-efficacy) and a more general indicator of school experience (satisfaction with school). Methods: The first model comprises 5,681 primary students (M=9.05; SD=.79), and the second 10,017 secondary students (M=14.20; SD=1.04) from Lima, Peru. In both models, the influence of grit and self-control on school satisfaction was observed when taking self-efficacy as a mediator variable. Results: The results show that grit and self-control have strong associations in both primary and secondary students. When estimating the covariance of both constructs, grit is related with academic-self efficacy at both educational stages, but only to satisfaction with school in secondary students. On the contrary, self-control shows a significant relationship with school satisfaction only in primary education. In turn, self-efficacy shows a mediating effect between grit and school satisfaction. After calculating the invariance of the models, differences are observed by gender in the relationships between variables. Conclusion: The results indicate that both constructs are strongly interrelated. Regarding the associations with the indicators of academic success, a need for timely interventions specific to each educational stage is observed.